d-Galactose Decreases Anion Exchange Capability through Band 3 Protein in Human Erythrocytes - Alessia Remigante; Rossana Morabito; Sara Spinelli; Vincenzo Trichilo; Saverio Loddo; Antonio Sarikas; Silvia Dossena; Angela Marino (MDPI AG, 2020)
d-Galactose (d-Gal), when abnormally accumulated in the plasma, results in oxidative stress production, and may alter the homeostasis of erythrocytes, which are particularly exposed to oxidants driven by the blood stream. In the present investigation, the effect of d-Gal (0.1 and 10 mM, for 3 and 24 h incubation), known to induce oxidative stress, has been assayed on human erythrocytes by determining the rate constant of SO42− uptake through the anion exchanger Band 3 protein (B3p), essential to erythrocytes homeostasis. Moreover, lipid peroxidation, membrane sulfhydryl groups oxidation, glycated hemoglobin (% A1c), methemoglobin levels (% MetHb), and expression levels of B3p have been verified. Our results show that d-Gal reduces anion exchange capability of B3p, involving neither lipid peroxidation, nor oxidation of sulfhydryl membrane groups, nor MetHb formation, nor altered expression levels of B3p. d-Gal-induced %A1c, known to crosslink with B3p, could be responsible for rate of anion exchange alteration. The present findings confirm that erythrocytes are a suitable model to study the impact of high sugar concentrations on cell homeostasis; show the first in vitro effect of d-Gal on B3p, contributing to the understanding of mechanisms underlying an in vitro model of aging; demonstrate that the first impact of d-Gal on B3p is mediated by early Hb glycation, rather than by oxidative stress, which may be involved on a later stage, possibly adding more knowledge about the consequences of d-Gal accumulation.